Associations of VEGF and CA125 with disease stage and pain among women with endometriosis: A cross-sectional study in Indonesia - Sujudi, Akmal; Rusnaidi, Rusnaidi; Rajuddin, Rajuddin; Septivera, Yusra; Dewi, Tgk. Puspa (Narra Sains Indonesia, 2026)
Endometriosis is a chronic gynecological disease characterized by the presence of endometrial tissue outside the uterine cavity, affecting approximately 10% of women of reproductive age. Vascular endothelial growth factor (VEGF) and cancer antigen 125 (CA125) have been proposed as potential biomarkers in endometriosis; however, evidence regarding their association with disease stage and pain severity remains limited, particularly in the Indonesian population. The aim of this study was to evaluate the relationship between peritoneal fluid VEGF and serum CA125 levels with endometriosis stage and pain severity. A cross-sectional study was conducted involving patients with surgically and histopathologically confirmed endometriosis who underwent laparoscopy or laparotomy at Dr. Zainoel Abidin Hospital, Banda Aceh, between February and July 2025. Peritoneal fluid VEGF and serum CA125 levels were measured using enzyme-linked immunosorbent assay and chemiluminescence immunoassay, respectively. Endometriosis stage was classified according to the revised American Society for Reproductive Medicine (rASRM) criteria, and pain severity was assessed using the Numeric Rating Scale. Statistical analyses included Spearman’s correlation and receiver operating characteristic (ROC) curve analysis. Our data suggested no significant correlation between VEGF levels and endometriosis stage (r=0.042; p=0.813). Peritoneal fluid VEGF levels showed a moderate positive correlation with pain severity (r=0.505; p<0.05), and ROC analysis identified an optimal cut-off value of 39.45 pg/mL, with a sensitivity of 73.68% and specificity of 73.33% for distinguishing severe pain from mild-to-moderate pain. Serum CA125 levels demonstrated a significant positive correlation with endometriosis stage (r=0.422; p=0.013), and ROC analysis yielded an optimal cut-off value of 32.45 U/mL, with a sensitivity of 86.95% and a specificity of 63.64% for distinguishing stage IV endometriosis from lower stages. No significant correlation was observed between CA125 levels and pain severity (r=0.186; p=0.292). This study represents the first report from Indonesia to simultaneously evaluate peritoneal fluid VEGF and serum CA125 in relation to endometriosis stage and pain severity. This study highlights that CA125 is primarily associated with endometriosis stage, whereas VEGF is more closely related to pain severity, supporting their complementary roles in endometriosis assessment.